Applied of CCME Water Quality Index for Evaluation of Water Quality of Euphrates river For Irrigation Purposes in Al-Nassiryia city - بهلول, مروج عباس (University of Thi-Qar Journal of Science, 2014)
The present work describes the application of Canadian Council of Ministers of the Environment Water Quality Index (CCME WQI) for irrigation uses for the 4 stations located along with Euphrates river in Al-Nassiryia city, Iraq. The field work was conducted during the period from summer 2012 to spring 2013.CCME WQI was applied using eleven water quality parameter (Sodium Adsorption Ratio (SAR), Residual Sodium Carbonate (RSC), Electric conductivity , pHvalue, Bicarbonate, Chloride Ion, Boron Ion, Lead, Iron, Cadmium, Copper). Based on the results obtained from the index, the values of water quality index for irrigation uses of Euphrates River ranged between 63.44-43.77 which indicate that river has Moderate quality for irrigation. The highest deviation occurred in SAR,Cl-,EC,